Intraoperative Prediction of Post-Operative Flap Outcome using the Near-Infrared Fluorophore Methylene Blue - Ashitate, Yoshitomo (2013)
Methylene blue (MB) is a near-infrared (NIR) fluorophore that provides a stable visual map of skin perfusion after intravenous injection. We explored the capability of MB to predict submental flap postoperative outcome using a single intraoperative measurement. Submental flaps were created in N = 15 pigs and imaged using the FLARE (™) imaging system immediately after surgery and at 72 h. Using the first 3 pigs, optimal MB dosing was found to be 2.0 mg/kg. Training and validation sets of 6 pigs each were then used for receiver operating characteristic (ROC) analysis. In the training set, a contrast-to-background ratio (CBR) threshold of 1.24 provided the highest sensitivity and specificity to predict tissue necrosis at 72 h. In the validation set, this threshold provided a prediction sensitivity of 95.3% and a specificity of 98.0%. We demonstrate that a single intraoperative NIR measurement can predict submental flap outcome at 72 h.